2019
DOI: 10.1038/s41467-019-09221-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory nanomedicines synergize with checkpoint blockade immunotherapy to eradicate colorectal tumors

Abstract: Nanoparticles can potentially stimulate tumour microenvironments to elicit antitumour immunity. Herein, we demonstrate effective immunotherapy of colorectal cancer via systemic delivery of an immunostimulatory chemotherapeutic combination in nanoscale coordination polymer (NCP) core-shell particles. Oxaliplatin and dihydroartemesinin have contrasting physicochemical properties but strong synergy in reactive oxygen species (ROS) generation and anticancer activity. The combined ROS generation is harnessed for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
160
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(162 citation statements)
references
References 62 publications
(51 reference statements)
0
160
1
1
Order By: Relevance
“…Recent studies have shown that the immune status of the tumor microenvironment is an essential factor affecting tumor progression. 4,[6][7][8] Both innate and adaptive immunity in the tumor microenvironment have been intensively investigated. In recent years, T-cell-based immunotherapy has shown benefits and provided hope for countless patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the immune status of the tumor microenvironment is an essential factor affecting tumor progression. 4,[6][7][8] Both innate and adaptive immunity in the tumor microenvironment have been intensively investigated. In recent years, T-cell-based immunotherapy has shown benefits and provided hope for countless patients.…”
Section: Introductionmentioning
confidence: 99%
“…Just to mention one example, dihydroartemisinin (DHA), a widely employed drug to treat malaria, contains a peroxide bridge that produces ROS in the presence of Fe 2+ as a catalyst. This drug has been co-delivered in combination with oxalilplatin in a controlled manner in solid tumors employing coordination polymer-based nanoparticles [81]. DHA release induced ROS formation within the tumoral cells, which altered their cell surface composition, causing CRT exposition and DAMP secretion, which enhanced APC recruitment.…”
Section: Nanoparticles To Enhance the Antitumoral Action Of Adaptive mentioning
confidence: 99%
“…The most representative nanocarriers described in this section are represented in Table 2. [74] Enhanced survival of T cells Self-assembled amphiphilic peptide IDO inhibitors and PD-L1 antagonist Melanoma [75] Higher expression of CRT, TNF-α, INF-γ and IL-6 -higher APC maturation and higher T cell activation and infiltration Core-shell coordination polymers Photosensitizer/oxalilplatin and anti-PD-L1 Colorectal cancer [78] ROS generation which enhances expression CRT -T cell activation, memory effect coordination polymer Dihydroartemisinin and anti-PD-L1 Colorectal cancer [81] ICD tumoral cells, higher T cell activation and infiltration PLGA-PEI-PEG Dox and microRNA that silence PD-L1 Colon adenocarcinoma [82] Improve CD8+ T cell infiltration Lipid-dendrimer-calcium-phosphate siRNA that silence PD-L1 and plasmid encoding IL-2…”
Section: Nanoparticles To Enhance the Antitumoral Action Of Adaptive mentioning
confidence: 99%
“…In recent years, immunotherapy has been explored as a therapeutic treatment for CRC. Studies have shown that several immune cells modulate CRC response by infiltrating the CRC microenvironment [3,4]. Among these immune cells, type 2 innate lymphoid cells (ILC2s) are abundant in the gut to regulate the gut homeostasis [5,6].…”
Section: Introductionmentioning
confidence: 99%